Biết rằng :bz-cy/a=cx-az/b=ay-bx/c. Chứng minh rằng x:y:z=a:b:c
biết rằng bz-cy/a = cx-az/b = ay-bx/c
chứng minh x:y:z = a:b:c
biết rằng bz-cy/a = cx-az/b = ay-bx/c. chung minh x:y:z=a:b:c
bz-cy/a=cx-az/b=ay-bx/c
chứng minh rằng x:y:z=a:b:c
Biết rằng : \(\frac{bz-cy}{a}=\frac{cx-az}{b}=\frac{ay-bx}{c}\) hãy chứng minh x:y:z=a:b:c
cho bz-cy/a = cx-az/b = ay-bx/c . chứng minh x:y:z = a:b:c
CMR: {bz-cy}:{cx-az}:{ay-bx}=a:b:c thì x:y:z=a:b:c
cho bz-cy/a = cx-az/b = ay-bx/c . CM : x:y:z = a:b:c
biet bz-cy/a=cx-az/b=ay-bx/c.c/m x:y:z=a:b:c